DIFFERENCES OF DRUG SALES BEFORE AND DURING COVID-19 AT PHARMACY STORES IN LAMONGAN, EAST JAVA - Riana Prastiwi Handayani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Covid-19 became a concern in the world at the end of December 2019 and Indonesia was no exception. The virus entered Indonesia in March 2020 which caused Indonesian people to limit their activities outside. If they are sick, they choose to do self-medication first by buying medicine at pharmacy store for fear to visit health care facilities (puskesmas, hospitals and clinics). This study focused on finding out the difference between drug sales before and during the Covid-19 pandemic at pharmacy store. This study is an observational with a retrospective design with purposive sampling.Methods: The instrument used in this study to collected the data on drug sales is observation form. The study was conducted in two pharmacy stores in Lamongan, East Java. The results of the study at the first pharmacy store showed that drug sales during Covid-19 were more (1,396 drugs) than before Covid-19 (758 drugs) with p<0.05. Likewise in the second pharmacy store, sales of drugs during covid-19 were more (40,993 drugs) than before covid- 19 (40,062 drugs) with p> 0.05.Results: The results of the study at the first pharmacy store showed that drug sales during Covid-19 were more (1,396 drugs) than before Covid-19 (758 drugs) with p<0.05. Likewise in the second pharmacy store, sales of drugs during covid-19 were more (40,993 drugs) than before covid-19 (40,062 drugs) with p> 0.05.Conclusion: In conclusion, there is a difference between drug sales before covid-19 and during covid-19 where drug sales increased during covid-19.